Características morfofisiológicas de sementes e produção de girassol em função de boro no solo - Bonacin, Gisele A.; Rodrigues, Teresinha De J. D. [UNESP]; Cruz, Mara C. P. Da [UNESP]; Banzatto, David A. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2009)
An experiment was carried out in order to evaluate effects of boron applied to soil on the morphophysiological characteristics of sunflower seed (achene). The experiment was installed on November 17, 2000 in an experimental area at São Paulo State University - UNESP/FCAV, Jaboticabal, SP, in an oxisoil with the sunflower variety Embrapa V122-2000. The experimental design was a completely randomized block, with five doses of boron (0, 1, 2, 3 and 4 kg ha-1) with four replications. After full bloom (80-90% of open flowers), the following characteristics were evaluated during seven weeks: length, width and thickness, seed dry mass, water concentration and content, first counting of germination, final germination and oil content. Seed yield was also evaluated. There was no significant effect of boron application on seed characteristics evaluated 49 days after full bloom, and this result was associated to the initial content of boron in the soil (0.22 mg dm-3 extracted with BaCl2 1.25 g L-1), which is considered an average value. The mean yield of seeds was 2,559 kg ha-1.

Com o objetivo de se estudar o efeito de doses de boro sobre as características morfofisiológicas de sementes e a produção de girassol, cultivar Embrapa V122-2000, instalou-se um experimento em 17/11/2000, em área experimental da UNESP/FCAV, Jaboticabal, SP, em Latossolo Vermelho eutrófico de textura média. O delineamento foi o de blocos casualizados, com cinco doses de boro (0, 1, 2, 3 e 4 kg ha-1) em quatro repetições. Após o florescimento pleno (80-90% de flores abertas) se avaliaram semanalmente, as características das sementes: comprimento, largura e espessura, massa seca, concentração e conteúdo de água, primeira contagem da germinação, germinação final e teor de óleo. Pelos resultados obtidos não se constatou efeito significativo da aplicação de boro nas características das sementes avaliadas aos 49 dias após o florescimento pleno da cultura, o que foi atribuído ao teor inicial de boro no solo, 0,22 mg dm-3 (extraído com solução de BaCl2 1,25 g L-1) que, além de considerado médio, deve ter sido suficiente para o crescimento e desenvolvimento das sementes de girassol. A produtividade média foi de 2.559 kg ha-1.
Morphophysiological characteristics of seed and production of sunflower as a function of boron in soil
Keywords: Helianthus annuus; achenes; growth; micronutrient; Helianthus annuus; aquênios; crescimento; micronutriente